2005
DOI: 10.7863/jum.2005.24.6.755
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Use of Renal Perfusion Imaging by Means of Harmonic Sonography With a Microbubble Contrast Agent in Patients After Renal Transplantation

Abstract: The renal perfusion images obtained by means of harmonic sonography with a microbubble contrast agent constitute an effective sonographic technique for the evaluation of renal perfusion abnormalities after renal transplantation compared with a (99m)Tc-DTPA scan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
(34 reference statements)
0
11
0
1
Order By: Relevance
“…Subsequent studies have been performed in rat (13,31,41), rabbit (59), dog (63,64,68), swine (24,69), mouse (55,57), and isolated organs (54). Contrast ultrasound imaging of the kidney is not in widespread clinical use, although studies have demonstrated potential utility for evaluation of focal abnormalities (46) and in identifying rejection following renal transplant (14,27,28). Of particular note, Kleinert et al (30) showed that TTP correlated to GFR in a small study of scleroderma patients, and Kalantarinia et al (26) demonstrated an increase cortical blood velocity in healthy subjects following a high-protein meal.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have been performed in rat (13,31,41), rabbit (59), dog (63,64,68), swine (24,69), mouse (55,57), and isolated organs (54). Contrast ultrasound imaging of the kidney is not in widespread clinical use, although studies have demonstrated potential utility for evaluation of focal abnormalities (46) and in identifying rejection following renal transplant (14,27,28). Of particular note, Kleinert et al (30) showed that TTP correlated to GFR in a small study of scleroderma patients, and Kalantarinia et al (26) demonstrated an increase cortical blood velocity in healthy subjects following a high-protein meal.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with renal artery stenosis (Fig. 10) or other vascular abnormalities, the re-filling curve revealed an increased time-to-peak and reduced slope of the wash-in tract and maximum amplitude [49, [67][68][69][70]. Animal models were initially employed to assess the capabilities of CEUS in the detection of renal perfusion defects [71][72][73][74][75], which appear as single or multiple focal wedge-shaped areas of absent, diminished or delayed contrast enhancement in comparison to the adjacent renal parenchyma (Figs.…”
Section: Clinical Applications Of Organ Perfusionmentioning
confidence: 99%
“…Renal perfusion imaging by means of harmonic ultrasonography with a microbubble contrast agent will potentially be very useful for the evaluation of renal perfusion in patients who have undergone renal transplantation; it shows not only the global perfusion status but also the focal perfusion defect in transplanted kidneys. 32 …”
Section: Ultrasonographically Guided Biopsymentioning
confidence: 99%